Local sustainable development activities through the example of the Sucha Beskidzka district - Agnieszka Gołuszka; Marta Gollinger-Tarajko (Economic and Environmental Studies (E&ES), 2016)
The presented Sucha Beskidzka district situated in the małopolskie voivodeship (province) is an example of many different projects implemented for the benefit of inhabitants: installation of solar collectors, thermal modernization of public facilities, construction of modern waste screening plant as well as initiatives for natural values protection and promoting 'small homeland'. The aim of this paper is to present how the sustainable development goals can be achieved at local level bringing ecological, economic and social effects. A financial and economic analysis and environmental effects of completed projects lead to conclusions the activities implemented by the district undoubtedly improved the quality of life in the local community. Reducing emissions of harmful substances into the air fosters both population health and preservation of valuable natural areas in the district such as the Natura 2000 area covering the Babia Góra National Park. The use of renewable energy sources brings not only reduced heating costs but also lowered energy consumption. These activities had also a social dimension. The implementation of the programs undoubtedly increased ecological awareness among local community - the need to take care of the nearesr environment and the sense of regional identity among citizens.
Keywords: Q42; Q59; 330; sustainable development; local activities; quality of life improvement; renewable energy sources; Sucha Beskidzka district